Let's simplify the expression step by step:
\[ (7x^2 - 6x + 2) - (4x - 8) + (-6x^2 + 3x) \]
First, distribute the negative sign through the second set of parentheses:
\[ = (7x^2 - 6x + 2) - 4x + 8 + (-6x^2 + 3x) \]
Now, combine the terms:
-
Combine like terms for \(x^2\): \[ 7x^2 - 6x^2 = 1x^2 \]
-
Combine like terms for \(x\): \[ -6x - 4x + 3x = -7x \]
-
Combine constant terms: \[ 2 + 8 = 10 \]
Putting it all together, we get:
\[ x^2 - 7x + 10 \]
Thus, the final simplified expression is:
\[ \boxed{x^2 - 7x + 10} \]